Determinants of Market Outlet Choice for Smallholder Broiler Farmers in Leribe District of Lesotho - Lekhisa, Khutlang; Muroyiwa, Brian (Journal of Social and Development Sciences, 2024)
Smallholder broiler farmers struggle to access lucrative formal markets because of low economies of scale, high transaction costs, a lack of awareness of market demand, poor production practices that are not oriented towards meeting the quality and quantity required in the market, poor infrastructure that raises transaction costs, and post-harvest losses. Therefore, this study examined the socio-economic, market and institutional factors that influence broiler farmers’ choice of market outlets in Leribe. The study adopted a random utility maximization theory and transaction cost theory to explain the farmers’ decision process regarding the choice of marketing outlet available in the study area. A total of 114 respondents for this study were selected from five villages using a two-stage sampling technique. The survey data was collected through a structured questionnaire. The MVP model results revealed that gender, vehicle ownership, stock size, contract agreement and access to extension services significantly influenced the choice of market outlets. Therefore, this study recommends the government and development partners consider interventions that will increase broiler production such as enhancing credit access, promoting contract farming, group membership and providing institutional support. The study also recommends policies that will facilitate the adoption of Good Agricultural Practices (GAP) to improve farmers’ access to the lucrative formal market outlets available in the study area. The Government of Lesotho should adopt policies that aim at linking smallholder farmers to formal markets, encouraging contract farming and facilitating the adoption of a Market Information System (MIS) to harmonize the flow of market information among exchange partners in broiler marketing.